Determinantes da transparência pública: um estudo em municípios brasileiros sob a ótica da teoria da escolha pública - Baldissera, Juliano Francisco (2018)
Transparency is a challenge for the current and future reform of public administration. Transparency increases resource allocation efficiency, reduces problems between principal and agent, and discourages rent-seeking activities. Considering the theoretical assumptions of the Theory of Public Choice, man is a utility maximizer, selfish and rational, which would explain his actions against public management. This research aims to analyze the influence of socioeconomic, financial-budgetary and political factors on the index of active transparency and passive transparency of Brazilian municipalities. To do so, this research is a quantitative study, in which 3,550 Brazilian municipalities were selected, in which socioeconomic, financial-budgetary and political information were obtained. We used the multivariate analysis technique, more specifically the multiple linear regression method using the ordinary least squares (OLS) method, with cross-section data. The results show that population size captures the complexity of public administration and government, which justifies the fact that in these municipalities they are more likely to adopt e-government activities, so they are more transparent. The positive variation in municipal per capita income and education levels positively impacts the variation in the level of transparency. Brazilian geographical regions add different socioeconomic characteristics, which justifies being shown as a determinant of the level of transparency. Financial condition and municipal debt are associated with financial credibility and the government's ability to meet its payment commitments, so public managers are encouraged to disclose information as a mechanism to allow their actions to be monitored. Intergovernmental transfers have been shown to exert a negative influence on public transparency, since in Brazil, there are many resources that are transferred without a pre-defined condition or expense, causing flypaper effect. Policymakers engage in meaningful investment projects, and use transparency so that citizens can visualize this type of information. Political competition increases the care of the manager, so the same must justify and give more transparency of their actions. The right-wing political ideology and party coalition with the governor demonstrate that these aspects influence the level of transparency, which suggests that political and ideological stability and alignment justify the actions of public managers. Finally, managers in the first electoral mandate exert a negative influence on the level of transparency, since they are less experienced and do not want to show in this direction to show their inefficiencies.